Profitable direct marketing - Jay, Ros. (London ; Boston : International Thomson Business Press, 1998)
This book is about: Establishing a database; Upgrading and using the database; The creative dimension; Direc response advertising; Direct mail; Door-to-door marketing; Mail order; and Telemarketing.
Keywords: Marketing; Direct marketing -- Great Britain; Direct marketing